2018
DOI: 10.1007/s10570-018-2145-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparative moisture and heat sorption properties of fibre and shiv derived from hemp and flax

Abstract: Unlike many mineral-based insulation materials bio-based lignocellulosic fibre and shiv offer a number of benefits including thermal and hygroscopic properties. The microstructure, porosity and chemical compositions of the plant cell walls play a major role in the moisture exchange process. In this paper, the effects of microstructure, chemical composition, porosity and pore size distribution of both fibre and shiv, from hemp and flax plants, on both moisture and heat sorption were studied for the first time. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 51 publications
(61 reference statements)
2
16
0
Order By: Relevance
“…The effect of TG on the microstructural properties of combined minced samples was observed using SEM ( Figure 3 ). The microstructures of the combined minced samples were similar in terms of the presence of certain structural elements: loose plant mass, individual plant cells, starch grains, and fragments of hemp and flax fibres, similar to that described by Jiang et al [ 34 ], which are evenly distributed within the homogeneous meat mass.…”
Section: Resultssupporting
confidence: 80%
“…The effect of TG on the microstructural properties of combined minced samples was observed using SEM ( Figure 3 ). The microstructures of the combined minced samples were similar in terms of the presence of certain structural elements: loose plant mass, individual plant cells, starch grains, and fragments of hemp and flax fibres, similar to that described by Jiang et al [ 34 ], which are evenly distributed within the homogeneous meat mass.…”
Section: Resultssupporting
confidence: 80%
“…The difference in surface morphology between CNF and TOCNF/G film may affect the sensors’ gas response properties. At a particular relative humidity, moisture absorption on cellulose fibers depends on the microstructure, porosity, and the portion of the chemical composition [ 45 ]. Besides, the rough and porous structure of cellulose creates a large interfacial area that can immobilize functional molecules.…”
Section: Resultsmentioning
confidence: 99%
“…The results showed that the moisture buffer value was not a function of the bulk density of the materials. It depends on the moisture transfer and moisture storage capacity of the materials, which is highly linked to the porosity and chemical composition, pore size distribution and the pore structure (30,31).…”
Section: Resultsmentioning
confidence: 99%